2017
DOI: 10.1103/physrevd.95.014027
|View full text |Cite
|
Sign up to set email alerts
|

Quark orbital angular momentum in the MIT bag model

Abstract: We present the results for the Generalized Transverse Momentum Distribution related to quark Orbital Angular Momentum, i.e. F14, in the MIT bag model. This model has been modified to include the Peierls-Yoccoz projection to restore translational invariance. Such a modification allows to fulfill more satisfactorily basic sum rules, that would otherwise be less elegantly carried out with the original version. Using the same model, we have calculated the twist-3 GPD that corresponds to Orbital Angular Momentumà l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…While a number of model calculations of GTMDs is available by now [3,4,8,9,[18][19][20][21][22][23][24][25][26][27][28][29], for many years it was unknown how GTMDs can be measured. Only recently it was shown that GTMDs of gluons can, in principle, be accessed via diffractive di-jet production in deep-inelastic lepton-nucleon and lepton-nucleus scattering [30][31][32], as well as virtual photon-nucleus quasi-elastic scattering [27].…”
Section: Introductionmentioning
confidence: 99%
“…While a number of model calculations of GTMDs is available by now [3,4,8,9,[18][19][20][21][22][23][24][25][26][27][28][29], for many years it was unknown how GTMDs can be measured. Only recently it was shown that GTMDs of gluons can, in principle, be accessed via diffractive di-jet production in deep-inelastic lepton-nucleon and lepton-nucleus scattering [30][31][32], as well as virtual photon-nucleus quasi-elastic scattering [27].…”
Section: Introductionmentioning
confidence: 99%
“…The general physical meaning of L q is that it is the torque acting on a quark during the polarized DIS process [39,138]: Ji's L q is the OAM before the probing photon is absorbed by the quark, while the Jaffe-Manohar L q is the OAM after the photon absorption, with the absorbing quark kicked out to infinity. These two definitions of L q have been investigated with several models, e.g., [137,139], whose results are shown in Section 6.11.2.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These two definitions of L q have been investigated with several models, e.g. [137,139], whose results are shown in section 6.11.2.…”
Section: Definitions Of the Spin Sum Rule Componentsmentioning
confidence: 99%
“…The general physical meaning of L q is that it is the torque acting on a quark during the polarized DIS process [39,138]: Ji's L q is the OAM before the probing photon is absorbed by the quark, while the Jaffe-Manohar L q is the OAM after the photon absorption, with the absorbing quark kicked out to infinity. These two definitions of L q have been investigated with several models, e.g., [137,139], whose results are shown in Section 6.11.2.…”
Section: Definitions Of the Spin Sum Rule Componentsmentioning
confidence: 99%